Characteristics of ecosystem multifunctionality and influencing factors of different grassland types in temperate desert of Longzhong Loess Plateau - Li, Yali; He, Guoxing; Liu, Xiaoni; Ji, Tong (Frontiers in Plant Science, 2025)
IntroductionEcosystem multifunctionality (EMF) refers to the integrated capacity of an ecosystems to provide a variety of services and functions. It plays a crucial role in maintaining ecological balance and achieving sustainable grassland development. Grassland type is a classification unit based on dominant species within the grassland ecosystem. However, the response of EMF to grassland type is still unclear, and its influencing factors need to be studied in depth.MethodsIn this study, we investigated the distribution characteristics of EMF in the Longzhong Loess Plateau temperate desert under different grassland types (Kalidium foliatum type, Reaumuria songarica type, Salsola passerinum type, and Sympegma regelii type grasslands) and identified the key factors driving changes in EMF.Results and discussionThe results indicated the K. foliatum type grassland exhibited higher EMF and belowground ecosystem multifunctionality (BEMF) indices (0.80 and 0.77, respectively), significantly greater compared to R. soongorica type, S. passerine type, and S. regelii type grasslands (P< 0.05). EMF and BEMF were significantly correlated with plant factors (coverage, root-shoot ratio), soil factors (mean weight diameter, MWD and geometric mean diameter, GMD) (P< 0.05), and showed strong positive relationships with Simpson diversity index. Hierarchical partitioning further indicated that MWD and GMD explained 29.86% and 38.21% of the variance in EMF, respectively. Structural equation modeling revealed that soil factors (MWD, GMD), plant factors (coverage, root-shoot ratio), and Simpson diversity index collectively explained 86% of the variation in EMF. Soil factors primarily exerted direct effects and indirectly promoted EMF by enhancing plant factors, with a total effect of 0.921. These findings suggest that K. foliatum type grassland can maintain EMF through soil factors, thereby supporting the sustainable development of temperate desert ecosystems in the Longzhong region of the Loess Plateau.